2009
DOI: 10.1002/chem.200801501
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Fluorescent Probes Via Protection/Deprotection of Functional Groups: A Ratiometric Fluorescent Probe for Cu2+

Abstract: Herein a ratiometric fluorescent Cu(2+) probe was rationally constructed in a straightforward manner with the concept of aldehyde group protection/deprotection. The probe showed a ratiometric fluorescent response to Cu(2+) with a large emission wavelength shift (>100 nm) and displayed high selectivity for Cu(2+) over other metal ions due to distinct deprotection conditions. In addition, a Cu(2+)-promoted dethioacetalization mechanism was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…The m/z signals under negative ion mode ([M − H] − = 161. 19) was consistent with standard 7-hydroxycoumarin (M = 162.14) (Fig. S1, Supplementary data) and the 1 H-NMR signal of the isolated product of 1-Cu 2+ (b) was the same as standard 7-hydroxycoumarin (c) as shown in Fig.…”
Section: Reaction Mechanismsupporting
confidence: 66%
See 1 more Smart Citation
“…The m/z signals under negative ion mode ([M − H] − = 161. 19) was consistent with standard 7-hydroxycoumarin (M = 162.14) (Fig. S1, Supplementary data) and the 1 H-NMR signal of the isolated product of 1-Cu 2+ (b) was the same as standard 7-hydroxycoumarin (c) as shown in Fig.…”
Section: Reaction Mechanismsupporting
confidence: 66%
“…Toward this end, highly sensitive and selective fluorescence turn-on chemodosimeters for Cu 2+ have appeared in recent years [15][16][17][18][19][20][21][22]. However, some reported fluorescence turnon chemodosimeters require specific detection conditions such as high temperature [15,16], nonphysiological pH [17,18], long reaction time [15,18,19] or need an organic solvent [17][18][19][20][21], which are not applicable for real biological sample analysis. Therefore, it is quite essential to develop new fluorescence turn-on chemodosimeters with excellent performance for Cu 2+ under physiological conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Hydrolytic cleavage of the −HC=N− bond has been successfully used for the development of probe for the detection of metal ions (Gai et al, 2014;Vandana et al, 2013;Ashish et al, 2014) [20]. For instance, Lin et al reported a fluorescence-enhanced probe for Fe 3+ ion based on hydrolysis of bis(coumarinyl) Schiff base (Lin et al, 2009) [21a]. Samanta et al…”
Section: Introductionmentioning
confidence: 98%
“…In this work, to circumvent the intrinsic fluorescence quenching effect of iodide, we employed a novel strategy based on the redox reaction between iodide and Cu 2+ to develop a novel type of fluorescence turnon iodide probes. As part of our ongoing studies on fluorescent probes [30][31][32][33][34][35], we have recently constructed colorimetric probe F-L (Scheme 1) for Cu 2+ based on intramolecular charge transfer (ICT), and the binding mode has been studied in detail [30]. Importantly, upon binding to Cu 2+ , the emission of compound F-L is almost completely quenched due to the intrinsic fluorescence quenching character of paramagnetic Cu 2+ [30].…”
Section: Introductionmentioning
confidence: 98%